Characterization of the phenotype and function of PRELP+ fibroblast subtype in liver metastatic colorectal cancer - Dai, Yuting; Huang, Xingying; Sun, Min; Zhang, Shiyu; Yu, Weiqiang; Hu, Kongwang; Wu, Qiang; Wu, Qingfa (Frontiers in Genetics, 2025)
IntroductionFibroblasts are critical mediators of tumor progression and metastasis; however, their heterogeneity and specific functions in the context of colorectal cancer (CRC) liver metastases remain incompletely understood.MethodsWe performed single-cell RNA sequencing (scRNA-seq) analysis on relevant tissue samples. Subsequently, we validated our findings using immunofluorescence assays on histological slides from primary CRC with liver metastasis (mCC) and liver metastatic tumors (mLC). Further investigations included transcriptomic profiling, pseudotime trajectory analysis, multiplex immunofluorescence staining, and cell-cell communication analysis.ResultsOur scRNA-seq analysis identified a distinct PRELP-positive cancer-associated fibroblast (CAF) subtype that is associated with liver metastasis and tumor progression. These PRELP+ CAFs were predominantly enriched in mLC, less abundant in mCC, and rare in non-metastatic CRC (nCC). This distribution was confirmed by immunofluorescence. Transcriptomically, PRELP+ CAFs exhibit a unique signature defined by extracellular matrix components (e.g., PRELP, COLEC11, ITGBL1) and the activation of pro-tumor pathways such as TGF-β and Wnt signaling. Pseudotime analysis indicated they represent a terminal fibroblast differentiation state. Spatially, they colocalize with immune cells (T cells, B cells, plasma cells), and communication analysis suggests they foster an immunosuppressive microenvironment via APP-CD74 and collagen-CD44 signaling, thereby promoting immune evasion. The transcription factors NR2F2, JUN, and JUND were identified as key regulators of this CAF subtype.DiscussionThese findings provide crucial new insights into fibroblast heterogeneity within CRC liver metastases. We characterize PRELP+ CAFs as a specialized, terminally differentiated fibroblast population that contributes to immunosuppression and tumor progression, highlighting them as a potential therapeutic target for inhibiting metastatic advancement.